Surgical treatment of kidney cancer adult and child - Clarck, Omar; Sierra, Ruben (Cirugía del Uruguay, 1974)
In surgical treatment of renal cancer in both adults and children, the thoraco-abdominal approach is advisable. In the child the need far urgent diagnosis is greater and consequently approach may only be abdominal; in such cases it is useful to remember that Wilms' tumor is highly friable. The author winds up his report by stating which are, in his opinion, those conditions that render resection of such tumors impossible.